Hubungan Kompetensi dengan Peran Penyuluh Pertanian dalam Mengembalikan Kejayaan Lada Putih (Muntok White Pepper) di Provinsi Kepulauan Bangka Belitung - Virginia Chintyasari; Yudi Sapta Pranoto; Fournita Agustina (Journal of Integrated Agribusiness, 2019)
In terms of developmental achievement and improvement of agricultural production in Indonesia, agricultural counseling has an important role as a learning facility for farmers and their families. In order for it to have optimal effects, it is important to establish the competency levels of agriculture counselors. This research aims to 1) Describe the competency level of agriculture councelors and their role in the development of muntok white pepper in Bangka Belitung Islands Province, 2) Analyze the correlation between the agricultural counselor’s competence and the development of muntok white pepper in Bangka Belitung Islands Province. This research is conducted using survey method. There are 125 councelors selected using the simple random sampling method. Data is analyzed using qualitative descriptive analysis with likert scale tabulation and spearman’s rank correlation. The result show that the highest correlation between agricultural counselor’s competence level and the development of muntok white pepper in Bangka Belitung Islands Province is found in communication skill, technical knowledge/GAP of white pepper, and cooperation skill, meanwhile, the highest score of the role of agriculture counselor in the development of muntok white pepper in Bangka Belitung Islands Province is found in the category of involvement in performing their duties as facilitators, communicators, mediators, motivators, and educators. The correlation between competence level and the role of agricultural counselor is at significance level of 0,01 with two way test at 52,60 percent, which has positive correlation coefficient in moderate category.